1997
DOI: 10.1073/pnas.94.16.8842
|View full text |Cite
|
Sign up to set email alerts
|

A calcium responsive element that regulates expression of two calcium binding proteins in Purkinje cells

Abstract: Calbindin D28 encodes a calcium binding protein that is expressed in the cerebellum exclusively in Purkinje cells. We have used biolistic transfection of organotypic slices of P12 cerebellum to identify a 40-bp element from the calbindin promoter that is necessary and sufficient for Purkinje cell specific expression in this transient in situ assay. This element (PCE1) is also present in the calmodulin II promoter, which regulates expression of a second Purkinje cell Ca 2؉ binding protein. Expression of high le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 32 publications
1
38
1
Order By: Relevance
“…The Ca concentration in the tubular fluid might be involved in regulating RNA expression of CaBP-28k and NCX. This hypothesis is supported by the existence of so-called calcium responsive elements in the promoter region of the CaBP-28k gene in mice (Arnold and Heintz, 1997). However, in the present study, the increase of RNA expression of CaBP-28k…”
Section: Discussioncontrasting
confidence: 53%
“…The Ca concentration in the tubular fluid might be involved in regulating RNA expression of CaBP-28k and NCX. This hypothesis is supported by the existence of so-called calcium responsive elements in the promoter region of the CaBP-28k gene in mice (Arnold and Heintz, 1997). However, in the present study, the increase of RNA expression of CaBP-28k…”
Section: Discussioncontrasting
confidence: 53%
“…Calbindin D28k is a member of the large EF-hand family that is believed to function, in part, as a cytosolic calcium buffer, and encodes a calcium binding protein that is expressed in the cerebellum exclusively in PC. [27][28][29] Our results demonstrated that at 5 months after transplantation, there was an increased number of PC in treated mice as compared with affected, irradiation control mice. These findings were most likely due to the presence of retrovirally transduced, bone marrow-derived microglial cells in the CNS that were capable of secreting ASM in sufficient amounts to delay the disease-specific cell death in PC neurons.…”
Section: Discussionsupporting
confidence: 50%
“…The CaM1 and CAM3 genes have more than one polyadenylation site, and a total of five calmodulin transcripts may be produced (45). Evidence shows that these transcripts are differentially regulated and transcribed because their promoter sequences possess different combinations of transcription factor binding sites (3,22,57). Only the CaM2 and CaM3 gene mRNA levels in Amø showed changes (Tables 1 and 2) during Pcp, suggesting that there is differential control of calmodulin gene transcription in Amø.…”
Section: Discussionmentioning
confidence: 97%
“…Phosphatidylinositol (3,4,5)-triphosphate, the product of PI-3K enzymatic activity, mediates Akt-1 (also called protein kinase B) (1,18,29) activation. Akt-1 controls many prosurvival functions (9,10,11,13,23), making PI-3K activation a linchpin of survival signaling.…”
mentioning
confidence: 99%